Biofilm formation on different dental restorative materials in the oral cavity - Alexander-Simon Engel; Hagen Tizian Kranz; Marvin Schneider; Jan Peter Tietze; Andree Piwowarcyk; Thorsten Kuzius; Wolfgang Arnold; Ella A. Naumova (BMC, 2020)
Abstract Background Bacterial biofilms adhere to all tissues and surfaces in the oral cavity. Oral biofilms are responsible for the decay of human dental structures and the inflammatory degeneration of the alveolar bone. Moreover, oral biofilms on artificial materials influence the lifespan of dental prostheses and restoratives. Methods To investigate in vivo oral biofilm formation and growth, five different dental restorative materials were analyzed and compared to human enamel. The roughness of the materials and the human enamel control probe were measured at the start of the study. The dental restorative materials and the human enamel control probe were placed in dental splints and worn for 3 h, 24 h and 72 h. Results Scanning electron microscopy (SEM) revealed major differences between oral biofilm formation and growth on the materials compared to those on human enamel. Microbiological analyses showed that bacterial strains differed between the materials. Significant differences were observed in the roughness of the dental materials. Conclusions It can be concluded that material roughness affects biofilm formation on dental surfaces and restoratives, but other factors, such as surface charge, surface energy and material composition, may also have an influence.